DEVELOPMENT OF PODTOON ANIMATED-BASED LEARNING MEDIA IN THE INTRODUCTION TO MACROECONOMICS COURSE - Silaban, Putri Sari MJ; Putriku, Aurora Elise; Hasibuan, Novita Indah; Sembiring, Jessica Putri Br. (Jurnal Ilmiah Global Education, 2023)
The development of teaching materials into film form and based on podcast media is a novelty. This step is an innovative idea to deal with relatively easy learning during the COVID-19 pandemic. This study aims to determine the level of feasibility and effectiveness of Poodton animated film-based teaching materials in the introduction to macroeconomics courses that can improve student learning outcomes. This study uses research and development (R&D) methods using the ADDIE model. This research was conducted on third-semester students taking an Introduction to Macroeconomics course in the economics study program in the 2023/2024 academic year. The data analysis technique used is quantitative data analysis techniques. The results of the research showed that the teaching materials developed received good ratings from experts with an average feasibility score of 4,21 which is in the appropriate category. In the practical test, students also gave a positive response with an average overall score of 5,80 entering the practical category as well as the effectiveness test using the t-test table for a significant level α= 5% = 0,05 and df = 19, then t was obtained at tcount = 17,72 and ttab = 1,729 with the conclusion that tcount > ttab so that it can be said that there is effectiveness (significance). The development of teaching materials for introduction to macroeconomics courses based on Poodton animated films with a significance level of 5% is very effective.